SUBCLONING AND EXPRESSION OF HALOACID DEHALOGENASE GENE FROM Pseudomonas aeruginosa LOCAL STRAIN - (NIM: 20514005), NURLAIDA
Halogenated organic compounds have been used widely as pesticide, herbicide, and solvent for industrial purposes. Due to their toxicity and persistency, abundance of these compounds in the environment is unavoidable, which are considered as pollutants. A great number of researches have showed that many microorganisms, particularly bacteria, are able to decompose these compounds and produce nontoxic matters. A well-known method which has been developing rapidly to overcome the negative impacts of these compounds is called bioremediation. Bioremediation basically is a method that utilizing the ability of the microorganisms to solve environmental issues. Bacteria is able to degrades halogenated organic compounds based on fact that they have one gene or even more, in their chromosome, that produce enzymes, called dehalogenase. Dehalogenase is a kind of enzyme which catalyzes the breaking bond between halogen atom and hydrocarbon chain. Previous research has found that Pseudomonas aeruginosa local strain from Indonesia possess the ability in degrading monochloroacetate. The responsible gene for this degradation had been successfully isolated and characterized, namely paed-d, a 702 bp respectively in pGEM-T vektor and E. coli TOP10 host. This research is focused on subcloning the paed-d gene into pET-30a expression vector and introducing it into E. coli BL21 (DE3). A forward primer with EcoRI site, GAATTC and a reverse primer with HindIII site, AAGCTT were used in PCR to obtain the desired fragment for cloning with a correct orientation for expression. Bases sequences that were used in this research is 5Ã‚Â’-GAATTCATGCGCGCGATCCTGTTCGA-3Ã‚Â’ as forward primer and 5Ã‚Â’-AAGCTTTCAGGCCGAGGCCGCCAGTT-3Ã‚Â’ as reverse primer. The obtained amplicon was first cloned into pGEM-T, transformed into E. coli TOP10, confirmed by rePCR, analyzed by restriction digest, sub-cloned into pET-30a, and transformed into E. coli BL21 (DE3). As expected, the PCR using the designed primers gave rise ~750 bp fragment. Restriction analysis in pGEM-T and the rePCR confirmed this result. Blast result of the paed-d gene sequence that had been subcloned into pET-30a(+) to the paed-d gene sequence from the previous study shows 100% similiarity. Overexpression of this gene based on observation at SDS-PAGE has been successfully obtained where the resulted protein is more concentrated in pellet, as an inclusion body, rather than in supernatant. Expression of the recombinant gene using IPTG as inducer was analyzed using SDS-PAGE gave the best result on IPTG concentration at 0,01 mM and induction temperature was 4 oC. Size of the protein is estimated around 26 kDa. This result is confirmed by Expacy Protparam which predicted the molecular weight of haloacid dehalogenase is about 26,352 kDa. Prediction of tertiary structure of haloacid dehalogenase from Pseudomonas aeruginosa local strain is β-sheets flanked by α-helixes. By in silico analysis of this enzyme, it turned out that it contains 233 amino acid residues where the catalytic residue is predicted lies on aspartate number seven (Asp7).